Gastric Braunina cordiformis and a review of helminth parasitism in the finless porpoise (Neophocaena phocaenoides) - Lombardini, Eric; Haetrakul, Thanida; Kuit, Sui H.; Chansue, Nantarika (Brazilian Journal of Veterinary Pathology, 2019)
A pregnant adult female finless porpoise (Neophocaena phocaenoides) stranded off the coast of Phuket, Thailand and died during attempted rehabilitation. The cadaver was frozen for use in a Marine mammal stranding training event. During necropsy, the animal was observed to have approximately 60% of the gastric mucosa embedded with exophytic, heart shaped digenean trematodes interpreted to be Braunina cordiformis. Tissue samples were collected from the stomach to include the embedded parasites and these were evaluated histopathologically, confirming the diagnosis. This is the first report of Braunina cordiformis trematodes in Asian waters and the first report of the parasite in a finless porpoise.